PERKECAMBAHAN DAN VIGOR SEMAI Picrasma javanica Blume PADA BERB AGAI SUHU - Hadi Sutarno; Ning Wikan Utami (Research Center for Biology-Indonesian Institute of Sciences, 2008)
The successfull cultivation of useful plant largely depends on the quality of seeds, especially viability and germination vigor. Seed of Picrasma javanica Blume has potential use in the development of templates for new drugs, e. g. to treat malaria.For most species there is still little or no information about the suitable temperature regime for germination and seedling depelopment,therefore,it is interesting to study germination and seedling vigor of Picrasma javanica. The mature green were picked and cleaned before using for experiments.Germination was carried out in 24 compartments of a thermogradientbar apparatus.The temperature gradient extends from 4.8 to 41.6°C with 1.6°C steps from the first to the 24 th compartment. Twenty seeds were germinated in each compartment. Seeds were sown on 2 layers of filter-paper strips.Everyday for 77 days during germination the germinating seeds were recorded.For hilling experiments those seeds from compartment number 3 to number 13 of thermogradientbar apparatus were than removed to incubator 32°C for 28 days. On the seedling vigor, all germinating seed from incubator were removed for replanting in growth room with sand medium. The seedling establishment capacity in the different thermal regions can thus be identified. The results showed that seeds attained 50% germination after 43 days when placed at the gradientbar 22.4°C to 41.6°C with optimum temperature 36.8°C. A 28 days temperatuture pretreatment ranging gradually from 4.8°C up to 20.8°C has promoted germination significantly. Mechanism of pretreatment on low and high temperature was discussed.